Analisa Faktor-Faktor yang Mempengaruhi Audit Report Lag Tahun 2019 - 2020 - Susanto Salim, Natalia Ervina, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
There are go public entities that are late in publishing audited financial statements to Financial Services Authority. The timeliness of financial reports publication depends on audit report lag. The goal of this empirical study to find out the influence of profitability, liquidity, company size and audit firm size on audit report lag in property, real estate and building construction companies listed on the Indonesia Stock Exchange from 2019-2020. A quantitative approach is applied with multiple linear regression analysis by operating SPSS 25 software. The data used is secondary data that collected through financial statements and annual reports. The total samples obtained in this study were 60 data which were chosen by purposive sampling method. The results stated that profitability and company size partially have a negative significant influence on audit report lag. Meanwhile, liquidity and audit firm size partially have no significant influence on audit reporting lag.